Pengaruh Postpurchase Price Perception dan Postpurchase Performance Perceptions Terhadap Satisfaction - Danang Yudhiantoro (KINERJA, 2009)
University  needs  the  trust  from  people  with  quality  assurance,  quality control,  and  quality improvement.  The  quality  assurance  and  quality improvement  can  be  doing  with  national accreditation.  They  need  evaluation about  customer  satisfaction,  from  their  perception  about price, etc.Using linear regression with SPSS serial 16 to measure and explain the result from this concept,  the  overall  impact  of  Postpurchase  Price  Perception  and Postpurchase  Performance Perception on satisfaction is positive. The implications of these findings for research, practice, and theory are discussed.